CLINICAL TERMINOLOGY: the basis for the representation / categorization of information in the storieselectronic patient clinics - Orrego, Veronica Nancy (2018)
The objective of this document is to describe the experience of the Department of Health Informatics of the Hospital Italiano de Buenos Aires (HIBA) in the generation of a thesaurus, with the use of Snomed CT as reference vocabulary, and the modifications that it suffered until which became terminological services. To meet this objective we will show the main milestones to show the current functionalities.